Kreatywność za drutem kolczastym: archeologia i sztuka okopowa z pierwszowojennego obozu jenieckiego w Czersku (woj. pomorskie) - Kobiałka, Dawid (Folia Praehistorica Posnaniensia, 2019)
This article discusses the results of archaeological and anthropological research concerning material remains of a prisoner of war camp in Czersk (Pomeranian province, Poland) (Kriegsgefangenenlager Czersk). In the first part, I sketch a broader historical context related to building and functioning of the camp in forests around Czersk between 1914–1919. After that, the role and meaning of archaeological research on such type of archaeological sites are presented. In the third part, I focus on a very special category of the camp heritage which is called trench art. The last part of this paper is a case study where an assemblage of objects classified as trench art that was found at the camp is described and interpreted. This text aims at highlighting the value of such prisoners and camp’s heritage. Such material culture is a material memory of extraordinary prisoners’ creativity behind barbed wire. It makes one aware of how every piece of trash, rubbish was re-cycled during day-to-day life behind barbed wire.